Modified clay mineral loaded anthocyanin pH test paper, preparation method and application thereof
Patent Information
- Application Number
- CN202610936180.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]本申请实施例提供一种改性黏土矿物负载花青素的pH试纸及其制备方法、应用,以解决或缓解上面提出的一项或更多项技术问题
[0006]本申请的pH试纸具有较好的检测准确性,在光照、高温环境下的具有较好的显色稳定性和安全性。具体地,通过采用蒙脱石、高岭石、凹凸棒石、埃洛石、皂石、伊利石等层状天然黏土矿物作为花青素的固定剂,即所述花青素组分吸附或络合于所述改性固定剂的层间或表面,利用固定剂的层间域结构及表面电荷对花青素分子进行物理吸附和静电固定,有效抑制花青素在光照、高温及长期储存条件下的分解与褪色,显著提高了pH试纸的显色稳定性。通过在显色剂中引入Ca、Mg、K、Na、Fe、Zn、Cu、Mn、Co、Mo、Ni、Ti等活性金属组分,这些活性组分负载于所述固定剂层间或表面,与花青素分子发生配位或络合作用,调节花青素在不同pH条件下的结构转变行为,从而拓宽pH试纸的显色响应范围,并提高对细微pH变化的显色分辨率。将含有花青素、固定剂和活性组分的显色剂负载于滤纸上,显色剂与滤纸纤维结合紧密,不易脱落,使用时仅需蘸取待测液即可快速显色,操作简便。
Smart Images

Figure CN122922046A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of pH detection technology, and in particular to a pH test paper containing anthocyanins loaded with modified clay minerals, its preparation method, and its application. Background Technology
[0002] Currently, pH detection methods mainly include pH electrode methods, spectroscopic analysis methods, and test strip methods. Among these, pH test strips based on natural anthocyanins are widely used in rapid on-site testing due to their advantages such as ease of operation, low cost, no need for specialized equipment, and naked-eye visibility. However, when using natural anthocyanins directly as the chromogenic component, anthocyanins are easily affected by environmental factors such as light and temperature, resulting in photodecomposition or thermal decomposition. This means that in complex environments, the decomposition of the main component of the pH test strip can affect the color development effect. Furthermore, traditional natural pigment test strips have a wide color transition range, making it difficult to accurately distinguish between similar pH values. Therefore, it is necessary to provide a safe pH test strip with better color development stability and detection accuracy.
[0003] It should be noted that the above content is not necessarily prior art, nor is it intended to limit the scope of protection of this application. Summary of the Invention
[0004] This application provides a pH test paper for modified clay minerals loaded with anthocyanins, its preparation method, and its application, in order to solve or alleviate one or more of the technical problems mentioned above.
[0005] A first aspect of this application provides a pH test paper loaded with anthocyanins from modified clay minerals. The pH test paper comprises: a substrate and a colorimetric agent loaded on the substrate, wherein the substrate is filter paper, and the colorimetric agent comprises anthocyanins, a fixative, and an active component; The fixative includes at least one of montmorillonite, kaolinite, attapulgite, halloysite, soapstone, and illite; The active component includes at least one of Ca, Mg, K, Na, Fe, Zn, Cu, Mn, Co, Mo, Ni, and Ti.
[0006] The pH test strip of this application exhibits good detection accuracy and good color stability and safety under light and high temperature environments. Specifically, by using layered natural clay minerals such as montmorillonite, kaolinite, attapulgite, halloysite, soapstone, and illite as fixatives for anthocyanins, the anthocyanin components are adsorbed or complexed in the interlayer or surface of the modified fixative. The interlayer domain structure and surface charge of the fixative are used to physically adsorb and electrostatically fix the anthocyanin molecules, effectively inhibiting the decomposition and fading of anthocyanins under light, high temperature, and long-term storage conditions, thus significantly improving the color stability of the pH test strip. Furthermore, by introducing active metal components such as Ca, Mg, K, Na, Fe, Zn, Cu, Mn, Co, Mo, Ni, and Ti into the colorimetric agent, these active components are loaded in the interlayer or surface of the fixative and coordinate or complex with anthocyanin molecules, regulating the structural transformation behavior of anthocyanins under different pH conditions. This broadens the color response range of the pH test strip and improves the color resolution for subtle pH changes. A colorimetric reagent containing anthocyanins, fixatives, and active components is loaded onto filter paper. The colorimetric reagent is tightly bound to the filter paper fibers and is not easily detached. When using it, you only need to dip it into the test solution to quickly develop the color, making the operation simple.
[0007] A second aspect of this application provides a method for preparing pH test paper loaded with anthocyanins from modified clay minerals. The method includes the following steps: A colorimetric solution is provided, the colorimetric agent comprising anthocyanins, a fixative, an active ingredient, and ethanol; Filter paper is immersed in the colorimetric reagent solution to load the colorimetric reagent onto the filter paper, thus obtaining pH test paper; The fixative includes at least one of montmorillonite, kaolinite, attapulgite, halloysite, soapstone, and illite; The active component includes at least one of Ca, Mg, K, Na, Fe, Zn, Cu, Mn, Co, Mo, Ni, and Ti.
[0008] The method in this application embodiment is simple and easy to implement. It uses a modified fixative to effectively fix anthocyanins, keeping their structure stable and thus improving the accuracy of pH detection. Anthocyanins with a determined color change range are combined with the modified fixative to prepare a colorimetric agent, which is then loaded onto test paper filter paper through a drying process to obtain pH test paper.
[0009] A third aspect of this application provides a pH test paper for testing the pH of a solution made of modified clay minerals loaded with anthocyanins as described in the first aspect or prepared by the method described in the second aspect. Attached Figure Description
[0010] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the various drawings denote the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings depict only some embodiments disclosed in this application and should not be construed as limiting the scope of this application.
[0011] Figure 1 The color change graph of the pH test strip in Example 1 between 1.0 and 14.0 is shown. Figure 2 This is a color change graph of the pH test paper in Comparative Example 1 between 1.0 and 14.0; Figure 3 This is a color change graph of the pH test paper in Comparative Example 2 between 1.0 and 14.0; Figure 4 This is a graph showing the changes in absorbance of pH test strips from Example 1, Comparative Example 1, and Comparative Example 2 after exposure to strong light and high temperature using a UV spectrophotometer. Figure 5 This is a graph showing the colorimetric stability of pH test strips from Examples 1, 1, and 2 after strong light and high-temperature treatment. Detailed Implementation
[0012] The embodiments of this application are described in detail below. These embodiments are exemplary and are only used to explain this application, and should not be construed as limiting this application. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be combined with each other.
[0013] In this application, when numerical intervals (i.e., numerical ranges) are involved, unless otherwise specified, the distribution of selectable numerical values within the numerical interval is considered continuous, and includes the two endpoints of the numerical interval (i.e., the minimum and maximum values), as well as every numerical value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed in this application should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include percentage intervals, ratio intervals, proportion intervals, etc.
[0014] Techniques for preparing pH test strips using anthocyanins as pH colorimetric agents and attapulgite as adsorbents have been developed. Research has also focused on preparing pH indicator membranes using chitosan and hydroxypropyl methylcellulose as matrices loaded with purple sweet potato anthocyanins for food freshness monitoring. Furthermore, explorations have been conducted on preparing intelligent colorimetric membranes and pH test strips using purple cabbage anthocyanins as raw materials. All these techniques utilize the colorimetric properties of anthocyanins as they change with pH. However, these technologies suffer from several drawbacks. First, the detection accuracy is low. Traditional natural pigment test strips lack finely calibrated color change intervals with a 0.1 gradient, resulting in blurred color transitions and difficulty in accurately distinguishing similar pH values. Second, large-scale production is challenging. Some montmorillonite-loaded anthocyanin-based pH indicator materials employ complex nanocarrier modifications, leading to cumbersome procedures and high costs, making them unsuitable for mass production of test strips. Third, while targeted montmorillonite protection is used to address the structural instability of anthocyanins, the lack of an efficient adsorption and fixation mechanism between anthocyanins and the montmorillonite carrier, relying solely on simple physical mixing, fails to form a stable bond. Finally, the lack of gradient refinement and precise calibration of the anthocyanin pH color change interval results in insufficient detection resolution. Meanwhile, the lack of systematic optimization of key parameters such as pretreatment of natural clay montmorillonite, adsorption process, and drying method makes it difficult for the stability, accuracy, and repeatability of the test strips to meet actual use requirements.
[0015] Accordingly, a first aspect of this application provides a pH test paper loaded with anthocyanins from modified clay minerals. The pH test paper includes a substrate and a colorimetric agent loaded on the substrate. The substrate is filter paper, and the colorimetric agent includes anthocyanins, a fixative, and an active component. The fixative includes at least one of montmorillonite, kaolinite, attapulgite, halloysite, soapstone, and illite. The active component includes at least one of Ca, Mg, K, Na, Fe, Zn, Cu, Mn, Co, Mo, Ni, and Ti.
[0016] The pH test strip of this application exhibits good detection accuracy and good color stability and safety under light and high temperature environments. Specifically, by using layered natural clay minerals such as montmorillonite, kaolinite, attapulgite, halloysite, soapstone, and illite as fixatives for anthocyanins, the anthocyanin components are adsorbed or complexed in the interlayer or surface of the modified fixative. The interlayer domain structure and surface charge of the fixative are used to physically adsorb and electrostatically fix the anthocyanin molecules, effectively inhibiting the decomposition and fading of anthocyanins under light, high temperature, and long-term storage conditions, thus significantly improving the color stability of the pH test strip. Furthermore, by introducing active metal components such as Ca, Mg, K, Na, Fe, Zn, Cu, Mn, Co, Mo, Ni, and Ti into the colorimetric agent, these active components are loaded in the interlayer or surface of the fixative and coordinate or complex with anthocyanin molecules, regulating the structural transformation behavior of anthocyanins under different pH conditions. This broadens the color response range of the pH test strip and improves the color resolution for subtle pH changes. A colorimetric reagent containing anthocyanins, fixatives, and active components is loaded onto filter paper. The colorimetric reagent is tightly bound to the filter paper fibers and is not easily detached. When using it, you only need to dip it into the test solution to quickly develop the color, making the operation simple.
[0017] The above-mentioned active components are loaded into the interlayer structure and surface of the fixative to form a modified fixative. The modified fixative is mixed with anthocyanins, and the active component ions form stable active centers in the clay interlayer, enhancing the electrostatic attraction and coordination ability of anthocyanins. Then, it is loaded onto filter paper to obtain pH test paper.
[0018] As a specific example, the fixative is montmorillonite, and the active component is copper or iron.
[0019] In some embodiments, the mass ratio of anthocyanin, the fixative, and the active component in the colorimetric agent is (1-12):(20-40):10. This allows the pH test paper to have better colorimetric properties and better stability.
[0020] In some embodiments, the loading of the colorimetric reagent in the pH test paper is 5 wt% to 30 wt%. This maintains the filter paper's appropriate porous structure, allowing the test solution to quickly wet and diffuse, and controlling the color development time within a short period.
[0021] A second aspect of this application provides a method for preparing pH test paper loaded with anthocyanins from modified clay minerals. The preparation method includes the following steps: (1) A colorimetric solution is provided, wherein the colorimetric agent comprises anthocyanin, a fixative, an active component, and ethanol. The fixative comprises at least one of montmorillonite, kaolinite, attapulgite, halloysite, soapstone, and illite, and the active component comprises at least one of Ca, Mg, K, Na, Fe, Zn, Cu, Mn, Co, Mo, Ni, and Ti.
[0022] (2) Immerse the filter paper in the colorimetric reagent solution so that the colorimetric reagent is loaded onto the filter paper to obtain pH test paper.
[0023] The method in this application embodiment is simple and easy to implement. It uses a modified fixative to effectively fix anthocyanins, keeping their structure stable and thus improving the accuracy of pH detection. Anthocyanins with a determined color change range are combined with the modified fixative to prepare a colorimetric agent, which is then loaded onto test paper filter paper through a drying process to obtain pH test paper.
[0024] Step (1) provides a colorimetric solution, which includes anthocyanins, a fixative, an active component, and ethanol. Ethanol has good solubility for anthocyanins and has little impact on the molecular structure of anthocyanins, thus maximizing the retention of the pH-responsive activity of anthocyanins. In the ethanol medium, the interlayer domains of the fixative can be moderately expanded, which is beneficial for the intercalation or surface loading of anthocyanin molecules and metal active components. The active components (Ca, Mg, Fe, etc.) can form uniform ions or complexes in ethanol, which can fully contact the fixative and anthocyanins, providing conditions for subsequent electrostatic adsorption or coordination fixation. The low surface tension of ethanol helps the colorimetric solution to uniformly wet the filter paper fibers, avoid local agglomeration, and the resulting test paper has good color uniformity.
[0025] In some embodiments, the colorimetric reagent solution is formed by: providing an ethanol solution of anthocyanins; first mixing the fixative and the active component oxide to obtain a modified fixative; and second mixing the modified fixative and the anthocyanin ethanol solution to obtain the colorimetric reagent solution. This stepwise formation method, which first modifies the active component oxide with the fixative and then mixes it with the anthocyanin ethanol solution, avoids direct interference of the active component with anthocyanins, significantly improving the loading stability of anthocyanins and the colorimetric sensitivity of the pH test paper.
[0026] Furthermore, the anthocyanin ethanol solution is formed by: obtaining multiple ethanol solutions with different ethanol concentrations; adding anthocyanin to each ethanol solution to form multiple anthocyanin ethanol saturated solutions corresponding to different ethanol concentrations; testing the absorbance of each anthocyanin ethanol saturated solution, and calculating the anthocyanin content based on the absorbance, with the ethanol concentration corresponding to the maximum anthocyanin content as the target ethanol concentration. By measuring the absorbance of anthocyanin saturated solutions in ethanol of different concentrations, selecting the ethanol concentration corresponding to the maximum absorbance as the optimal ethanol concentration (target ethanol concentration) can maximize the solubility of anthocyanins, thereby improving the anthocyanin loading and color development performance in the colorimetric reagent solution.
[0027] Optionally, the concentration of ethanol in the ethanol solution is 10 vol% to 100 vol.
[0028] As a specific example, six 100 mL volumetric flasks were used to prepare ethanol solutions with volume fractions of 10 vol%, 30 vol%, 50 vol%, 70 vol%, 90 vol%, and 100 vol%, respectively. Anthocyanin extract was added to each concentration of ethanol solution in portions of 0.1 g, stirring for 2 minutes each time, until the solution reached saturation (a slight, persistent turbidity appeared). After standing for 15 minutes, the solution was filtered, and the saturated anthocyanin ethanol solutions of each concentration were collected. A spectrophotometer was used to scan the wavelength range of 480 nm to 600 nm to determine the optimal absorption wavelength λmax. The absorbance of each concentration of saturated solution was measured at this wavelength, and the ethanol concentration corresponding to the maximum absorbance was taken as the optimal ethanol concentration.
[0029] In some embodiments, prior to the first mixing, the fixative is dried at 70°C to 100°C for 1 h to 3 h and then passed through a 150-300 mesh sieve. This yields a pretreated fixative.
[0030] In some embodiments, the mass ratio of the fixative to the active component oxide is (2~4):1, for example, 2:1, 3:1, 4:1, etc. This ensures that the active component is fully loaded into the interlayer or surface of the fixative to form an effective modified fixative, while avoiding excessive active component that could lead to fixative aggregation or blockage of interlayer channels, thereby achieving the best fixative modification effect and anthocyanin loading stability.
[0031] In some embodiments, the temperature of the first mixing is 300 ℃ to 500 ℃, for example, 300 ℃, 400 ℃, or 500 ℃. This allows the active component to be uniformly inserted into the interlayer structure of the fixative or firmly loaded onto its surface, forming a structurally stable modified fixative. At the same time, it avoids insufficient loading due to excessively low temperatures or damage to the layered structure of the fixative due to excessively high temperatures, thereby obtaining the best modification effect and subsequent anthocyanin fixation ability.
[0032] As a specific example, the fixative is montmorillonite. Montmorillonite was dried in an oven at 80 °C for 2 hours, then passed through a 200-mesh standard sieve to obtain purified, original blank clay montmorillonite mineral powder for later use. Montmorillonite was then modified by loading metal ions using different ratios of active component oxides and montmorillonite at 400 °C to prepare single-factor modified montmorillonite.
[0033] In some embodiments, during the second mixing process, the solid-liquid ratio is 1:(15~30) g / ml. This ensures that the modified fixative is fully dispersed in the anthocyanin ethanol solution and achieves effective loading of anthocyanins, avoiding the problem of fixative agglomeration and uneven loading due to an excessively high solid-liquid ratio, or anthocyanin waste due to an excessively low solid-liquid ratio, thereby obtaining optimal loading efficiency and color development performance.
[0034] In some embodiments, the temperature of the second mixing is 15 ℃ to 50 ℃, such as 15 ℃, 25 ℃, 30 ℃, 40 ℃, 50 ℃, etc.
[0035] In some embodiments, the second mixing time is 10 min to 100 min, such as 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, etc.
[0036] As a specific example, the curing agent is slowly added in batches to an anthocyanin saturated solution with the optimal ethanol concentration at a solid-liquid ratio of 1g:(20~50)mL, and magnetically stirred at a certain temperature for 10 min~100 min to allow the anthocyanin molecules to be fully adsorbed on the surface and / or between the layers of the modified fixative.
[0037] In some embodiments, after the second mixing and before obtaining the colorimetric solution, the method further includes: allowing the impregnated material to stand and filtering it; redispersing the filtered material in a saturated ethanol solution and ultrasonically dispersing it for 5 min to 20 min at a solid-liquid ratio of 1 g: (30~60) mL, thereby obtaining a colorimetric solution with better purity.
[0038] Furthermore, the fixative is montmorillonite, which has a layered silicate structure and a large specific surface area. Its surface carries a negative charge, enabling it to firmly fix anthocyanin molecules between layers or on the surface through physical adsorption and electrostatic attraction. Single-factor experiments can examine the influence of each variable on the adsorption effect one by one. By comparing the adsorption rates at different levels, the optimal process conditions for the most complete binding of anthocyanins with clay minerals can be identified.
[0039] In step (2), filter paper is immersed in the colorimetric reagent solution to load the colorimetric reagent onto the filter paper, thus obtaining pH test paper. By immersing the filter paper in the colorimetric reagent mixture, the colorimetric reagent can be uniformly and firmly loaded onto the surface and pores of the filter paper fibers, thereby obtaining pH test paper with uniform color development, rapid response, and good stability. In some embodiments, the impregnation time is 30 s to 40 s, such as 30 s, 33 s, 35 s, 37 s, 40 s, etc. This further enhances the impregnation effect.
[0040] In some embodiments, after impregnation and before obtaining pH test paper, the impregnated filter paper is dried at a temperature of 30°C to 40°C for 20 to 30 minutes to adjust the initial color depth of the test paper. The main component of the filter paper is cellulose, which contains a large number of hydroxyl groups, enabling it to form hydrogen bonds with the surface of clay minerals, firmly attaching the anthocyanin-loaded clay mineral particles to the fiber surface. Anthocyanins are sensitive to high temperatures; excessively high temperatures can cause structural damage or degradation, while low-temperature or room-temperature drying can protect the active structure of anthocyanins.
[0041] In some embodiments, 28 small test tubes are prepared with aqueous solutions ranging from pH 1.0 to 14.0, and the pH gradient interval is controlled at 0.5. 2 mL of colorimetric reagent is added to each test tube, and after standing for 10 minutes, the color change is observed using a colorimeter. For the color abrupt change range, a pH gradient of 0.1 to 1 is further set for refined measurement to determine the precise color change node. The color change range of the composite colorimetric solution is measured using gradient pH solutions, with a further refined measurement of 0.1 to 1 gradients for the color abrupt change range. Simultaneously, a colorimeter is used to assist in observing color changes, replacing purely visual judgment. The molecular structure of anthocyanins undergoes a reversible transformation with pH changes, and this transformation is particularly dramatic at certain pH points. The colorimeter can quantify the color, eliminating subjective differences in human judgment and improving data accuracy and repeatability. The color changes from red to pink at pH 2.2 and from purple to blue at pH 11.2, significantly improving the accuracy of pH detection and providing a scientific basis for the accurate interpretation of test strips.
[0042] A third aspect of this application provides a pH test paper for testing the pH of a solution made of modified clay minerals loaded with anthocyanins as described in the first aspect or prepared by the method described in the second aspect.
[0043] Exemplary embodiments according to this application will now be described in more detail with reference to the accompanying drawings. It should be understood that these exemplary embodiments may be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein.
[0044] Example 1 Take six 100 mL volumetric flasks and prepare ethanol solutions with volume fractions of 10 vol%, 30 vol%, 50 vol%, 70 vol%, 90 vol%, and 100 vol%, respectively. Add anthocyanin extract to each concentration of ethanol solution in portions, adding 0.1 g each time and stirring for 2 minutes until the solution reaches saturation (a slight, persistent turbidity appears). After standing for 15 minutes, filter and collect the saturated anthocyanin ethanol solutions of each concentration. First, dilute the solution appropriately to bring it within the measurement range of the UV spectrophotometer. Then, adjust the pH value to 1.0 and 4.5, respectively, and use the UV spectrophotometer to measure the absorbance of each concentration of saturated solution under the two pH conditions at wavelengths of 520 nm and 700 nm (corrected for turbidity). Calculate the final absorbance of the saturated solution using the pH differential method, expression (1).
[0045] (1).
[0046] Then, the anthocyanin content in each saturated solution is calculated using the μg anthocyanin-3-glucoside equivalent (μg CGE / g DW) per g dry weight, as expressed in expression (2).
[0047] (2).
[0048] Where A represents the final absorbance calculated using interpolation; MW represents the average molecular weight of anthocyanin (e.g., cyanidin-3-glucoside, 449.2 g / mol); and DF represents the dilution factor. Expressed as molar extinction coefficient (e.g., 26900 L / (mol·cm) for cyanidin-3-glucoside). l It is expressed as the optical path of the cuvette (usually 1 cm).
[0049] Finally, through the above measurements and calculations, the anthocyanin contents extracted from 10 vol%, 30 vol%, 50 vol%, 70 vol%, 90 vol%, and 100 vol% ethanol solutions were found to be 263.84 mg / L, 507.65 mg / L, 890.48 mg / L, 754.79 mg / L, 622.04 mg / L, and 614.26 mg / L, respectively. The maximum absorbance corresponds to the highest anthocyanin content in the ethanol solution; therefore, 50 vol% is considered the optimal concentration for anthocyanin extraction with ethanol.
[0050] Montmorillonite was dried in an oven at 80 °C for a provisional time of 2 h, and then passed through a 200-mesh standard sieve to obtain pretreated clay montmorillonite mineral powder for later use. Montmorillonite was prepared by loading metal ions onto montmorillonite and iron oxide at 400 °C using different mass ratios of 3:1.
[0051] Add 5g of modified montmorillonite to 150 mL of the above saturated solution at a solid-liquid ratio of 1g:30 mL, stir magnetically at 25 °C for 40 min, let stand for 10 min, and then filter through a 0.45 μm filter membrane. Redisperse the filter cake in 150 mL of 50 vol% ethanol solution and sonicate for 10 min to obtain the composite colorimetric solution.
[0052] Prepare 20 mL of standard gradient aqueous solutions with pH values ranging from 1.0 to 14.0 (intervals of 0.5) in 28 test tubes. Add 2 mL of composite colorimetric solution to each tube, let stand for 10 min, and then measure using a colorimeter: pH 1.0–2.0 is red, pH 2.5–3.0 is pink, pH 3.5–10.5 is purple, pH 11.0–12.0 is blue, and pH 12.5–14.0 is yellow. Refine the gradient by 0.1 for the abrupt changes in pH 2.0–2.5 and pH 10.5–11.5 to determine the precise color change points. Refer to the RAL color chart to determine the colors displayed at different pH values. See the attached table for specific results. Figure 1 And Table 1, Figure 1 (a) shows the color change of the pH test strip in Example 1 in the range of 1.0 to 5.5; Figure 1 (b) Color change of the pH test strip in Example 1 in the range of 6.0 to 10.5; Figure 1 (c) Color change of the pH test strip in Example 1 in the range of 11.0 to 14.0. The color scale division value of the above pH change is 0.5.
[0053] The qualitative filter paper was cut into 1 cm × 5 cm test strips, immersed in the above composite colorimetric solution for 35 s, removed and drained of excess solution, and dried at 40 ℃ for 25 min to obtain pH test strips.
[0054] Table 1
[0055] The above Figure 1 Table 1 shows that the pH test strip of this application can form distinguishable color changes under different pH conditions, with minimal overall deviation and high matching degree with theory; combined with the stability and color difference test results described later, it can be seen that its color change is basically without deviation under normal, light and high temperature conditions; the high temperature deviation is slightly higher than that of pure montmorillonite, far better than that of pure anthocyanin, and has good color development retention ability and color change node stability.
[0056] Comparative Example 1 pH test paper was prepared in accordance with the method of Example 1, except that unmodified montmorillonite was added.
[0057] Prepare 20 mL of standard gradient aqueous solutions with pH values ranging from 1.0 to 14.0 (intervals of 0.5) in 28 test tubes. Add 2 mL of composite colorimetric solution to each tube, let stand for 10 min, and then detect the color using a colorimeter: pH 1.0–2.0 is red, pH 2.5–3.0 is pink, pH 3.5–10.5 is purple, pH 11.0–12.0 is blue, and pH 12.5–14.0 is yellow. The gradient was refined by 0.1 for the abrupt changes in pH 2.0–2.5 and pH 10.5–11.5 to determine the precise color change points. See [link to results] for details. Figure 2 And Table 2, Figure 2 (a) shows the color change of the pH test paper in Comparative Example 1 in the range of 1.0 to 5.5; Figure 2 (b) Color change of pH test paper in Comparative Example 1 in the range of 6.0 to 10.5; Figure 2 (c) Color change of the pH test paper in Comparative Example 1 in the range of 11.0 to 14.0. The color scale division value of the above pH change is 0.5.
[0058] Table 2
[0059] Figure 2 Table 2 shows that the pH test paper with unmodified montmorillonite exhibits delayed color change at the acidic end and earlier color change at the alkaline end; the acidic end loses its color change after light exposure; and the alkaline end nodal at high temperature is basically consistent with the theory.
[0060] Comparative Example 2 pH test paper was prepared in accordance with the method of Example 1, except that the active component iron and modified montmorillonite were not added.
[0061] Prepare 20 mL of standard gradient aqueous solutions with pH values ranging from 1.0 to 14.0 (0.5 intervals) in 28 test tubes. Add 2 mL of composite colorimetric solution to each tube, let stand for 10 min, and then measure using a colorimeter: pH 1.0–2.0 is red, pH 2.5–3.0 is pink, pH 3.5–10.5 is purple, pH 11.0–12.0 is blue, and pH 12.5–14.0 is yellow. Refine the gradient by 0.1 for the abrupt changes in pH 2.0–2.5 and pH 10.5–11.5 to determine the precise color change points. Refer to the RAL color chart to determine the colors displayed at different pH values. See [link to RAL color chart] for specific results. Figure 3 And Table 3, Figure 3 (a) shows the color change of the pH test paper in Comparative Example 2 in the range of 1.0 to 5.5; Figure 3(b) Color change of pH test paper in Comparative Example 2 in the range of 6.0 to 10.5; Figure 3 (c) Color changes of the pH test paper in Comparative Example 2 in the range of 11.0 to 14.0. The color scale division value of the pH changes mentioned above is 0.5.
[0062] Table 3
[0063] Figure 3 Table 3 shows that pH test strips containing only anthocyanins exhibit the largest shift in color change node at the alkaline end, abnormal color change path, and missing multiple hue transition segments; they completely lose their normal color change ability after light exposure; and the acidic end is delayed by more than 3.5 pH units at high temperatures.
[0064] Figures 1-3 The summary in Tables 1-3 shows the following color retention rates: Example 1 > Comparative Example 1 > Comparative Example 2; color stability: Example 1 > Comparative Example 1 > Comparative Example 2; color change node shift: Example 1 > Comparative Example 1 > Comparative Example 2. This indicates that the modified fixative significantly enhances the light and heat resistance of anthocyanins through adsorption protection. Simultaneously, the color retention ability of the test strip under harsh environments and its room temperature storage stability were verified, providing a shelf-life basis for its practical application.
[0065] Figure 4 The graph shows the absorbance changes of pH test strips from Examples 1, Comparative Example 1, and Comparative Example 2 after exposure to strong light and high temperature using a UV-Vis spectrophotometer. The graph shows that the pH test strip from Example 1 has the highest absorbance (Abs≈2.7), indicating a high anthocyanin loading; its absorbance decreased by 55.6% after 24 hours of light exposure, with a complete peak shape; and its absorbance remained high even after heating at 50°C. This indicates that iron-modified montmorillonite effectively inhibits anthocyanin decomposition and fading through both physical adsorption and coordination. The pH test strip from Comparative Example 1 has the second highest absorbance (Abs≈1.9); its absorbance decreased by 57.9% after 24 hours of light exposure, showing a higher degree of degradation than Example 1; and its absorbance decreased by approximately 90% after heating at 50°C. This demonstrates that relying solely on the physical adsorption of pure montmorillonite without coordination protection limits its light and heat protection capabilities. The pH test paper in Comparative Example 2 showed the lowest absorbance under normal conditions, indicating weak anthocyanin stability. After 24 hours of light exposure, the absorbance in the visible light region approached zero, indicating severe photodegradation of anthocyanins and loss of color development ability. At high temperatures, the absorbance decreased significantly, and the decomposition rate was rapid. Without mineral carrier protection, the molecular structure was rapidly destroyed in strong light and heat environments.
[0066] Figure 5This is a graph showing the colorimetric stability of pH test strips from Examples 1, 1, and 2 after strong light and high-temperature treatment, based on the color difference (ΔE). The graph shows that the pH test strip of Example 1 exhibits a normal ΔE of 0.78–6.96, with continuous color without abrupt changes; a stable curve under light (ΔE) of 4.35–8.81; and good thermal stability under heating (ΔE) of 3.25–6.40. The node offset is <1.0, indicating accurate pH response. The pH test strip of Comparative Example 1 exhibits a normal ΔE of 3.78–8.55, stable in the neutral region but with abrupt color changes; a change in brightness only under light (ΔE) of 3.04–5.52; and large fluctuations in the strongly alkaline region under heating (ΔE) of 3.41–9.02. The maximum node offset is +3.00, indicating poor accuracy. The pH test strips of Comparative Example 2 showed a large fluctuation in ΔE (2.81–9.27) under normal conditions, with obvious color abrupt changes; under light, the ΔE ranged from 4.90 to 13.70, and instability occurred at pH 3.5; under heating, the ΔE ranged from 1.62 to 11.30, with only brief stability within a narrow pH range. The maximum node offset was +3.50, indicating the worst accuracy.
[0067] It should also be noted that the terms "some embodiments," "other embodiments," and "embodiments" used in this application refer to specific features, structures, or characteristics described in connection with those embodiments, which are included in at least one embodiment described in the general description of this application. The appearance of the same expression in multiple places in the specification does not necessarily refer to the same embodiment. Furthermore, when a specific feature, structure, or characteristic is described in connection with any embodiment, the intention is to suggest that implementing such a feature, structure, or characteristic in conjunction with other embodiments also falls within the scope of this application.
[0068] In the above embodiments, the descriptions of each embodiment have different focuses. For parts not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.
[0069] It should also be noted that the above are merely preferred embodiments of this application and do not limit the scope of protection of this application. Any equivalent structural or procedural transformations made based on the content of this application's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the scope of protection of this application.
Claims
1. A pH test paper containing anthocyanins loaded with modified clay minerals, characterized in that, include: The filter paper and the color developer loaded on the filter paper, wherein the filter paper is filter paper and the color developer includes anthocyanins, a fixative and an active component; The fixative includes at least one of montmorillonite, kaolinite, attapulgite, halloysite, soapstone, and illite; The active component includes at least one of Ca, Mg, K, Na, Fe, Zn, Cu, Mn, Co, Mo, Ni, and Ti.
2. The pH test paper with modified clay minerals loaded with anthocyanins according to claim 1, characterized in that, In the colorimetric agent, the mass ratio of anthocyanin, the fixative, and the active component is (1~12):(20~40):
10.
3. The pH test paper with modified clay minerals loaded with anthocyanins according to claim 1, characterized in that, In the pH test paper, the loading of the colorimetric reagent is 5 wt% to 30 wt%.
4. A method for preparing pH test paper loaded with anthocyanins from modified clay minerals, characterized in that, Includes the following steps: A colorimetric solution is provided, the colorimetric agent comprising anthocyanins, a fixative, an active ingredient, and ethanol; Filter paper is immersed in the colorimetric reagent solution to load the colorimetric reagent onto the filter paper, thus obtaining pH test paper; The fixative includes at least one of montmorillonite, kaolinite, attapulgite, halloysite, soapstone, and illite; The active component includes at least one of Ca, Mg, K, Na, Fe, Zn, Cu, Mn, Co, Mo, Ni, and Ti.
5. The preparation method according to claim 4, characterized in that, The color developer solution is formed by the following methods: Provide an ethanol solution of anthocyanins; The fixative and the active component oxide are first mixed to obtain the modified fixative; The modified fixative and anthocyanin ethanol solution are mixed a second time to obtain a colorimetric solution.
6. The preparation method according to claim 5, characterized in that, The anthocyanin ethanol solution is formed as follows: Obtain multiple ethanol solutions with different ethanol concentrations; Anthocyanins were added to each ethanol solution to form multiple anthocyanin-saturated ethanol solutions with different ethanol concentrations. The absorbance of a saturated anthocyanin ethanol solution is tested to determine the target ethanol concentration, which is the ethanol concentration corresponding to the maximum absorbance.
7. The preparation method according to claim 5, characterized in that, Before the first mixing, the process further includes: drying the fixative at 70 ℃~100 ℃ for 1 h~3 h and passing it through a 150 mesh~300 mesh sieve; The mass ratio of the fixative to the active component oxide is (2~4):1; The temperature of the first mixture is 300 ℃ to 500 ℃.
8. The preparation method according to claim 5, characterized in that, The second mixture satisfies at least one of the following conditions: The solid-liquid ratio is 1:(15~30)g / ml; Temperature 15℃~50℃; Time: 10 min to 100 min.
9. The preparation method according to claim 4, characterized in that, The immersion time is 30 s to 40 s; And / or, after impregnation and before obtaining pH test paper, the impregnated material is dried at a temperature of 30 ℃ to 40 ℃ for 20 min to 30 min.
10. The application of the pH test paper of modified clay mineral loaded with anthocyanins according to claims 1 to 3 or the pH test paper of modified clay mineral loaded with anthocyanins obtained by any one of claims 4 to 9 in testing the pH of a solution.